IMPLEMENTATION OF LOCAL HISTORY-BASED LEARNING METHODS IN INCREASING STUDENTS' HISTORICAL AWARENESS IN HISTORY SUBJECTS: QUALITATIVE STUDIES IN CLASS XI-1 SMA NEGERI 11 MEDAN - Aditya Darma; Surya Aymanda Nababan; Muhammad Ricky Hardiyansyah; Nur’aini (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2026)
This study aims to examine the implementation of local history-based learning methods in increasing students' historical awareness in history subjects in Class XI-1 Social Studies SMA Negeri 11 Medan. The research uses a qualitative approach with a case study type. Data collection was carried out through participant observation, in-depth interviews, and documentation studies. The results of the study show that the implementation of local history-based learning methods is carried out through structured planning, implementation, and evaluation stages by integrating the Medan Area Battle as the main topic of local history. This method has a positive impact on students' historical awareness which is reflected in increasing understanding of local historical events, the ability to connect the past with the present, and internalizing the values of struggle such as nationalism and patriotism. Supporting factors for implementation include teacher commitment, student enthusiasm, and the rich history of the city of Medan, while the inhibiting factors are limited learning resources, time allocation, and facilities and infrastructure. This study concludes that local history-based learning is effective as a strategic alternative to increase students' historical awareness while strengthening their cultural identity (Asril, Ahmal, Nurdiansyah, & Pernantah, 2025; Nababan, 2025). The research recommends the development of more adequate local history learning resources as well as training for teachers in implementing a locality-based approach. Keywords: Local History-Based Learning, Historical Awareness, History